2022
DOI: 10.3390/s22239294
|View full text |Cite
|
Sign up to set email alerts
|

Application of Digital Twins and Metaverse in the Field of Fluid Machinery Pumps and Fans: A Review

Abstract: Digital twins technology (DTT) is an application framework with breakthrough rules. With the deep integration of the virtual information world and physical space, it becomes the basis for realizing intelligent machining production lines, which is of great significance to intelligent processing in industrial manufacturing. This review aims to study the application of DTT and the Metaverse in fluid machinery in the past 5 years by summarizing the application status of pumps and fans in fluid machinery from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…In the maritime sector, DTT can expedite the development of digital representations of the marine industry. For instance, Yang et al (2022) [106] summarized the current application status of pumps and fans in fluid machinery from the perspectives of DTT and Metaverse. Research found that DTT and Metaverse technology played a crucial role in the development of new pump products and technologies, and were widely used in numerical simulation and fault detection of various pumps and other fields of fluid machinery.…”
Section: Research Prospect Of Dtt In the Marine Industrymentioning
confidence: 99%
“…In the maritime sector, DTT can expedite the development of digital representations of the marine industry. For instance, Yang et al (2022) [106] summarized the current application status of pumps and fans in fluid machinery from the perspectives of DTT and Metaverse. Research found that DTT and Metaverse technology played a crucial role in the development of new pump products and technologies, and were widely used in numerical simulation and fault detection of various pumps and other fields of fluid machinery.…”
Section: Research Prospect Of Dtt In the Marine Industrymentioning
confidence: 99%
“…These technologies have the potential to facilitate the creation of personalized experiences, enhance decision-making processes, and enable more efficient interactions between users and the digital environment. Scholars in this cluster also stress the role of digital twins and the IoT in shaping the metaverse landscape [136][137][138]. For example, Lv et al [137] stated that digital twins provide a virtual representation of physical assets or processes, allowing for real-time monitoring, simulation, and optimization.…”
Section: Topic Modelingmentioning
confidence: 99%
“…Deductive reasoning has been used because it is systematic and focused on testing hypotheses. The process begins with the development of a theoretical framework, followed by the formulation of hypotheses that have been tested through the collection and analysis of empirical data [15]. The suggested work that attempts to combine mathematical programming and machine learning to enhance EDM, is ideally suited to this method.…”
Section: B Research Approachmentioning
confidence: 99%